PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN DI BANK MAYAPADA KCU MEGA MAS MANADO - Monsow, Endrokles Y; Runtuwene, Roy F; Rumawas, Wilhelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
This study aims to analyze the influence of knowledge management on employee performance at (Bank Mayapada main branch of Mega Mas) in Manado City. Samples are employees of May Mayada KCU Mega Mas Manado as many as 50 people drawn from 50 people from the total population of employees. Data collection techniques in this study are interviews and questionnaires. Data analysis technique used in this research is simple linear regression. The results show that knowledge management has a positive and significant impact on employee performance. implementation of knowledge management has a strong and significant relationship with employee performance. In general, Knowledge Management gives a positive influence on the performance of Bank Mayapada employees of KCU Mega Mas Manado, it is suggested that the company pay more attention to Knowledge Management program to get the result that is the improvement of employee performance as a result of the improvement of employee performance of Bank Mayapada Mega Mas Manado.Keywords: Knowledge Sharing, Employee Performance